2002
DOI: 10.1016/s0895-7061(02)02265-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic function in physiologic and pathologic hypertrophy

Abstract: Doppler echocardiographic parameters of LV diastolic function can be of diagnostic importance for discrimination between pathologic and physiologic LV hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…A significant increase in TGFb1 values and LVM/h 2.7 and a higher prevalence of subjects with left ventricular hypertrophy were found in the subset of hypertensives with diastolic dysfunction in comparison with patients with normal diastolic function. According to literature data [37][38][39][40] and to higher prevalence of LVH found in our hypertensives with altered diastolic function, TGFb1 overproduction might be able to affect diastolic function through an altered left ventricular geometry. Surprisingly, in our study, multivariate analysis indicated an independent role of TGFb1 in the occurence of alteration in left ventricular filling.…”
Section: Left Ventricular Filling Abnormalities and Obesity-associatementioning
confidence: 53%
See 1 more Smart Citation
“…A significant increase in TGFb1 values and LVM/h 2.7 and a higher prevalence of subjects with left ventricular hypertrophy were found in the subset of hypertensives with diastolic dysfunction in comparison with patients with normal diastolic function. According to literature data [37][38][39][40] and to higher prevalence of LVH found in our hypertensives with altered diastolic function, TGFb1 overproduction might be able to affect diastolic function through an altered left ventricular geometry. Surprisingly, in our study, multivariate analysis indicated an independent role of TGFb1 in the occurence of alteration in left ventricular filling.…”
Section: Left Ventricular Filling Abnormalities and Obesity-associatementioning
confidence: 53%
“…This hypothesis might be supported by the statement that, with the fibrotic remodelling process, an increase in the stiffness of left ventricular myocardium can lead to an early impairment of the diastolic function. 40 In addition, some clinical implications arise from the results of our study. In particular, an early recognition of altered left ventricular filling in the presence of the normal left ventricular systolic function may be beneficial in single subjects as well as in a strategy for general health care.…”
Section: Left Ventricular Filling Abnormalities and Obesity-associatementioning
confidence: 85%
“…This is commonly called physiologic LVH, as it is reversible and not associated with adverse effects [11,16]. Differentiating between physiologic LVH and pathologic LVH (such as LVH from hypertension) is of clinical importance.…”
Section: Physiologic Versus Pathologic Left Ventricular Hypertrophymentioning
confidence: 99%
“…Schannwell et al [16] recently studied 49 athletes with LVH due to endurance training, 49 patients with LVH due to hypertension, and 26 untrained healthy control subjects by Doppler echocardiography. There were comparable values for LV muscle mass and muscle mass index in the trained athletes (99 ± 10 g) and hypertensive patients (95 ± 11 g), both being much higher than those of the control group (52 ± 7 g; P < 0.01 for athletes and hypertensives).…”
Section: Physiologic Versus Pathologic Left Ventricular Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation